Thrombotic microangiopathy in the era of HIV - Davies, Malcolm (My University, 2014)
Human immunodeficiency virus (HIV) associated thrombotic microangiopathy (TMA) is thought to be a common form of the disorder in South Africa with a severe clinical presentation and poor prognosis; it remains however poorly characterized. This study was undertaken to evaluate the presentation and prognosis of HIV-associated TMA through retrospective analysis of a cohort of HIV positive and negative subjects diagnosed with and treated for TMA at a single center (Helen Joseph Hospital) from 1/1/2001 to 31/12/2009. HIV-associated TMA was the dominant form of the disorder in this series and was associated with advanced HIV infection and a more severe presentation than TMA in HIV negative subjects. Although mortality was non-significantly more frequent, response to plasmapheresis was more rapid and recurrence less common in HIV positive subjects. This study adds to available literature on a rarely studied disorder. Despite its aggressive nature, timeous diagnosis and intervention facilitate satisfactory outcomes in HIV-associated TMA.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Internal Medicine Johannesburg, 2014
Keywords: HIV; Thrombotic Microangiopathies